Slutsky and Hicksian Equation in the View of Sharia Economics (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Meanwhile, from an Islamic economic perspective, demand and supply are the same as conventional economics. However, there are restrictions for individuals to act economically in accordance with Sharia (the Quran and Sunnah as well as the Ijtihad of Islamic scholars or economists). Slutsky's theory explains the behavior of consumers who allocate income to maximize consumption satisfaction, which is acceptable in Islam as long as it does not violate the principle of moderation. Price and Income Impact: Islam teaches us to consider the impact of prices and income on the economic balance of individuals and society, In Islamic economics, Islamic norms and moral values are used as principles in economics The Hicksian theory, which focuses on consumer satisfaction, is acceptable if it does not neglect the spiritual aspect. Price and Income Impact: Islam encourages its followers to consider the impact of the economy on social welfare. The Hicksian theory helps to understand how changes in prices and income affect consumption decisions. Islam criticizes the assumption that consumers are always rational and have complete information, as humans have limitations and weaknesses..